História, educação e relações Brasil-EUA : Robert King Hall e o programa de construção de escolas rurais do INEP (1949-1951) - Cunha, Adriana Mendonça (2018)
The purpose of this work is to analyze the contribution of the American researcher Robert King Hall to the rural education program, coordinated by the National Institute of Pedagogical Studies (INEP, in Brazilian portuguese), at the 1940 decade, in Brazil. The project, launched by the government in 1946, aimed to promote a greater qualification of labor on the field, contain rural exodus and fight high rates of illiteracy. INEP was responsible for organization, coordination and inspection of rural school construction, besides promoting the training of the teachers who would act in those institutions. Hall was hired by the institute to work as a technician, teaching an improvement course for teachers and to produce an analysis of the program. Using Pierre Bourdieu’s concepts of Field and Scientific Capital, we seek to evaluate the role played by Hall in Brazilian educational field from the position occupied by him as a foreign researcher and the stablished relations with the institutions and the intellectuals with whom he kept in contact. For this, we exam the reports produced by the American researcher about the program, published in the Brazilian Magazine of Pedagogical Studies, newspaper articles, laws and decrees referring to rural education. Our goal was to identify Hall’s postures related to Brazilian rural education and to evaluate level of influence exerted by the researcher in the project he contributed with. Written in a time marked by the emergence of the Cold War, Hall’s texts stablished a direct relation between democracy and education, assigning to this a determinative role in the national development process. As a foreign researcher, and collaborator of the INEP, Hall did a critical analysis of the program, pointing changes to be executed in the project, many of them also defending by Brazilian intellectuals since the 1930’s. At the same time he proposed a rural teaching model based in American experience and references.